2015
DOI: 10.1007/s00345-015-1617-1
|View full text |Cite
|
Sign up to set email alerts
|

Classification of stress urinary incontinence

Abstract: While SUI classification is potentially relevant to treatment selection, evidence for influence on management outcome is limited. Generating a high-quality evidence base for treatment selection on these criteria is problematic, particularly due to the range of confounding factors. In practice, the modern practitioner relies on various tools to form an opinion on some key aspects, using the findings to derive a treatment strategy. Accordingly, there remains a need to confirm how a classification of SUI translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 21 publications
0
20
0
5
Order By: Relevance
“…Twelve to 40% of all patients with stress urinary incontinence (SUI) are affected by intrinsic sphincter deficiency (ISD), that is defined as an urodynamic maximal urethral closure pressure (MUCP) of ≤20 cm H 2 O . Various reasons may lead to this poor urethral closure mechanism, such as age‐related reduction of muscle mass, nerve or muscle dysfunction, previous surgery, or a neurological disease . Patients with ISD are especially difficult to treat .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve to 40% of all patients with stress urinary incontinence (SUI) are affected by intrinsic sphincter deficiency (ISD), that is defined as an urodynamic maximal urethral closure pressure (MUCP) of ≤20 cm H 2 O . Various reasons may lead to this poor urethral closure mechanism, such as age‐related reduction of muscle mass, nerve or muscle dysfunction, previous surgery, or a neurological disease . Patients with ISD are especially difficult to treat .…”
Section: Introductionmentioning
confidence: 99%
“…dysfunction, previous surgery, or a neurological disease. 4,5 Patients with ISD are especially difficult to treat. 4 Standard tension-free vaginal tape (TVT) therapy of the entire SUI population has a 6-month success rate of 93.1%, 6 and success rates for 32 months, 7 or 11 years still are considerably high (87%, 7 81%, 8 or 77%, 9 respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Because the loosened pelvic floor muscle causes the migration of the urethral sphincter distally in older women, the decreased urethral closure pressure and urethral closure dysfunction during abdominal stress caused by urethral hypermobility lead to female stress incontinence [16,17]. We showed that the urethral sphincter migrates proximally after RP, thereby increasing urinary incontinence.…”
Section: Discussionmentioning
confidence: 76%
“…Not only VLPP is affected by the bladder volume but it is also affected by the detrusor pressure at some extent. The Cystometography (CMG) can miss about 50% of cases [14] of a detrusor contraction-related incontinence and this condition is associated with higher bladder volumes. Higher bladder volumes mildly increase the detrusor pressure which opens the urethra sphincters and VLPP demonstrated at these bladder volumes might reflect the external sphincter function instead of the internal sphincter function.…”
Section: Discussionmentioning
confidence: 99%
“…Technically, VLLP is a dynamic test that measures the proximal urethra and bladder neck response to abdominal pressure [1] and its value allows the clinical classification of SUI [14][15][16] into urethra hypermobility and intrinsic sphincter deficiency. Originally suggested by McGuire [5,17] VLPP was used for the assessment of intrinsic sphincter dysfunction (ISD) patients with SUI.…”
Section: Introductionmentioning
confidence: 99%